The Johannesburg fresh produce market: an analysis of its operations and contribution to the food system - Malungane, Makhanana; Wegerif, Marc C. A. (Frontiers in Sustainable Food Systems, 2025)
The Johannesburg Fresh Prouce Market (JFPM) is the largest fresh produce market in Africa, in terms of volume and turnover. It plays a central role in making fresh produce accessible across Gauteng Province and surrounding areas. This article describes and analyses the operations of the JFPM giving attention to the social and economic forces that shape it and looking at its contribution within the food system. The research for this article was conducted from between 2019 and 2023, including extensive interviews with 127 research participants and observations conducted during over 60 visits to the Market. It is found that the JFPM involves a complex interaction between economic and social forces still influenced by apartheid era arrangements. This influence is evident in the long-term social relationships among actors of the same ethnic and cultural backgrounds. The findings also highlight the importance of the JFPM as a source of fresh produce, especially for low-income neighbourhoods through the multitudes of informal traders that source produce there. By making fresh produce more accessible and enabling the agency of diverse actors in the food system, the JFPM makes a key contribution to food security. The Market is also essential for farmers, large and smaller scale, who sell there. The positive role of the JFPM is under threat from a range of challenges ranging from internal issue such as decaying infrastructure to external factors, such as the increasing use of direct buying focused supply chains by supermarket groups. Given the important contributions of the JFPM it needs to be invested in and maintained. The lessons from this market have relevance to food markets in other contexts.